2012
DOI: 10.1021/ol3011024
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst- and Solvent-Free Click Synthesis of Cyclodextrin-Based Polyrotaxanes Exploiting a Nitrile N-Oxide

Abstract: A catalyst- and solvent-free synthesis of cyclodextrin-based polyrotaxanes exploiting a stable nitrile N-oxide as an end-capping agent was achieved. The C-C bond-forming end-capping reaction of an allyl-terminated pseudopolyrotaxane with the nitrile N-oxide proceeded smoothly by solid-state grinding in a mortar to afford a polyrotaxane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Takata et al demonstrated that no catalyst was required to synthesize [ n ]rotaxanes under solvent‐free conditions when using dipolar cycloaddition between nitrile N ‐oxides and alkenes to interlock PEG‐ and PTHF‐based polyrotaxanes (Scheme ) . The threading of the allyl‐terminated linear guests through the cavities of α‐CD or PMα‐CD was achieved in solution through three sequential steps: (a) sonication (room temperature, 30 min), (b) standing overnight at room temperature, and (c) collecting the solid precipitate through centrifugation.…”
Section: Stoppering Through 13‐dipolar Cycloadditionsmentioning
confidence: 99%
“…Takata et al demonstrated that no catalyst was required to synthesize [ n ]rotaxanes under solvent‐free conditions when using dipolar cycloaddition between nitrile N ‐oxides and alkenes to interlock PEG‐ and PTHF‐based polyrotaxanes (Scheme ) . The threading of the allyl‐terminated linear guests through the cavities of α‐CD or PMα‐CD was achieved in solution through three sequential steps: (a) sonication (room temperature, 30 min), (b) standing overnight at room temperature, and (c) collecting the solid precipitate through centrifugation.…”
Section: Stoppering Through 13‐dipolar Cycloadditionsmentioning
confidence: 99%
“…Building upon our previous study, [24][25][26][27][28][29][30][31][32][33][34][35][36] we selected bis(2-alcoxy-naphthalene nitrile N-oxide) as a skeleton, speculating that it should serve well as a framework for a sufficiently-stabilized homoditopic nitrile N-oxide. Synthesis of the homoditopic nitrile N-oxide 1 was accomplished in 58% overall yield via a three-step reaction (Scheme 1, m.p.…”
Section: Synthesis Of Bis(nitrile N-oxide) 1 and Poly(boron Enaminokementioning
confidence: 99%
“…applications not only to polymeric materials but also supramolecular chemistry because we have previously reported effective synthesis of rotaxane and polyrotaxane exploiting a cycloaddition of stable nitrile N-oxide. 16,27,30,33,36 The study of stimuli-responsive fluorescent switching system using BEK-containing supramolecular skeleton will be important for future. …”
Section: Synthesis Of Bis(nitrile N-oxide) 1 and Poly(boron Enaminokementioning
confidence: 99%
“…This agent enables the easy molecular integration of various nucleophiles onto C=C-, C≡C-, and C≡N-containing polymers in the presence of an appropriate catalyst. Building on our previous reports [23][24][25][26][27][28][29][30][31][32], in this study, we describe a convenient protocol to introduce a masked ketene moiety to 4 unsaturated-bond-containing common polymers via a catalyst-free click reaction.…”
Section: Introductionmentioning
confidence: 99%